APPLICATIONS FOR CHILDREN HOMEPAGE ENGLISH USING MACROMEDIA DREAMWEAVER MX - Inda Ratnawati; Yuce Yuliani , SKom, MMSI (Jurnal Sistem Informasi, 2007)
Internet is now become a choice of the most effective in disseminating information because the internet has a vast network coverage. One gets a large portion of the information on the internet include information relating to education, particularly English language education. This information is conveyed through one of the storage media on the internet information homepage or website. English is the language of the world. In all areas, especially in the field of information technology, all using English. English should be introduced at an early age, so that future generations of children to become an outstanding successor. This scientific writen trying to explain how making a homepage on studying English. Starting from design stage to the homepage ready to be published on the internet. All were created using Macromedia Dreamweaver MX software to design the homepage.